Nematodes of the order Rhabditida from Tehran province (Iran). Some known species of the family Cephalobidae (Journal of Nematode Morphology and Systematics, 2012)
Nine species of the family Cephalobidae are described from natural areas in Tehran province (Iran): Acrobeloides nanus, Cephalobus persegnis, Cervidellus hamatus, C. vexilliger, Eucephalobus mucronatus, E. oxyuroides, E. striatus, Nothacrobeles prominens and Stegelleta ophioglossa. Excepting C. vexilliger, these species are reported from Iran for the fi rst time. Description, measurements and illustrations are presented for all species, and SEM pictures for some of them. N. prominens is a rare species which has been previously reported from Europe; Iranian specimens agree well with those recorded from Hungary and Italy. The second record of SEM observations of S. ophioglossa and new data on SEM observations of C. hamatus are also provided.